Secure and privacy–preserving, timed vehicular communications. (13th September 2012) - Burmester, Mike; Magkos, Emmanouil; Chrissikopoulos, Vassilis
We consider the problem of privacy and security of routine safety messages in vehicular (V2V) communication. Traditional public key mechanisms are not appropriate because of the large number of messages that have to be transmitted. We first show that a recently proposed scheme, the TSVC based on TESLA is subject to an impersonation attack, and propose a modification that secures it. We then propose a communication scheme based on a variant of TESLA, for which packets are self–authenticating and combine both schemes to get a hybrid scheme that addresses in a flexible way the mobility requirements of V2V communications.